Pengaruh pengungkapan ESG dalam laporan keberlanjutan terhadap nilai perusahaan pada perusahaan subsektor batubara di bursa efek Indonesia - Winowattan, Maria Fransisca; Oktrivina, Amelia (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2026)
This study analyzes the impact of Environmental, Social, and Governance (ESG) disclosure on firm value, using Return on Equity (ROE), firm size (SIZE), and Debt-to-Equity Ratio (DER) as control variables. The research focuses on coal subsector companies listed on the Indonesia Stock Exchange from 2020 to 2024, employing a quantitative approach with panel-data regression analysis. The Common Effect Model was found to be the most suitable after conducting model selection tests. While ESG disclosure did not significantly affect firm value as measured by Tobin’s Q, ROE positively affected firm value, whereas SIZE and DER negatively affected it. Collectively, ESG disclosure, ROE, SIZE, and DER significantly influence firm value, suggesting that coal sector investors prioritize financial performance over sustainability disclosures. Public interest statements The practical implications of this study indicate that companies, particularly in the coal sector, need to improve the quality and consistency of ESG disclosures as part of their business strategy to strengthen reputation, transparency, and firm value in the eyes of investors. For management, the findings can serve as a basis for formulating sustainability strategies and ESG reporting aligned with OJK regulations. Meanwhile, investors and stakeholders can use ESG information to more comprehensively assess a company's performance, risk, and long-term prospects